Kv1.3 Channel Inhibition Limits Uremia-Induced Calcification in Mouse and Human Vascular Smooth Muscle. Issue 1 (4th December 2020) - Cazaña-Pérez, Violeta; Cidad, Pilar; Navarro-González, Juan F; Rojo-Mencía, Jorge; Jaisser, Frederic; López-López, José R; Alvarez de la Rosa, Diego; Giraldez, Teresa; Pérez-García, Maria Teresa
Abstract: Chronic kidney disease (CKD) significantly increases cardiovascular risk. In advanced CKD stages, accumulation of toxic circulating metabolites and mineral metabolism alterations triggers vascular calcification, characterized by vascular smooth muscle cell (VSMC) transdifferentiation and loss of the contractile phenotype. Phenotypic modulation of VSMC occurs with significant changes in gene expression. Even though ion channels are an integral component of VSMC function, the effects of uremia on ion channel remodeling has not been explored. We used an in vitro model of uremia-induced calcification of human aorta smooth muscle cells (HASMCs) to study the expression of 92 ion channel subunit genes. Uremic serum-induced extensive remodeling of ion channel expression consistent with loss of excitability but different from the one previously associated with transition from contractile to proliferative phenotypes. Among the ion channels tested, we found increased abundance and activity of voltage-dependent K + channel Kv1.3. Enhanced Kv1.3 expression was also detected in aorta from a mouse model of CKD. Pharmacological inhibition or genetic ablation of Kv1.3 decreased the amount of calcium phosphate deposition induced by uremia, supporting an important role for this channel on uremia-induced VSMC calcification. Graphical Abstract: